Horizontal Mergers with Scale Economies - Davide Dragone; Luca Lambertini; Andrea Mantovani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2006)
We examine the profitability and social efficiency of horizontal mergers in a Cournot oligopoly with decreasing average costs. Assuming the merger allows for a reduction in the total amount of fixed costs, we identify the conditions under which the merger is, respectively, profitable and socially desirable. There exists an admissible parameter range wherein the merger is socially convenient but not profitable. In such a case, the policy maker may induce firms to merge through subsidies financed via a lump sum tax.
Keywords: 330; Fusion; Oligopol; Skalenertrag; Theorie